Ḍawābiṭ Fatwa dalam Merespons Problematika Fikih Kontemporer: Ḍawābiṭ Fatwa in Responding to Contemporary Fiqh Problems - Munira, Munira; Dewi Indriani; Andzala Cahyani (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
New or contemporary phenomena are always emerging along with the times. This requires a scientific answer or fatwa related to the problem, This research aims to find out the dawābiṭ fatwa in responding to contemporary fiqh problems. The problems raised by the author in this study are; First, what is the position of fatwa in resolving fiqh problems? Second, How is ḍawābiṭ fatwa in resolving contemporary fiqh problems? This research is a library research using normative and philosophical approach methods. The results of the study were found as follows; First, contemporary jurisprudence has a very important role in determining Islamic laws in the modern era. Second, ḍawābiṭ fatwa in resolving contemporary fiqh problems, namely: 1) Fatwa must be based on a deep understanding. 2) Analysis of complex problems with basic points. 3) The decision of the fatwa should not be hasty. 4) Fatwa decisions must involve experts in certain fields. 5) Fatwas must take into account differences in customs and traditions. 6) Fatwas must be made and based on experience. 7) The right fatwa must be based on the principles of fiqh. 8) Fatwa must be backed up or based on evidence and evidence. 9) The obligation of collective fatwas in the fatwas of the ummah and their priority over individual fatwas. 10) Fatwa must agree and be close to the mind regarding the rules of fiqh.